2013
DOI: 10.1016/j.jcmg.2012.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Native T1 Mapping in Differentiation of Normal Myocardium From Diffuse Disease in Hypertrophic and Dilated Cardiomyopathy

Abstract: This study demonstrates that native and post-contrast T1 values provide indexes with high diagnostic accuracy for the discrimination of normal and diffusely diseased myocardium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
269
4
12

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 411 publications
(307 citation statements)
references
References 32 publications
22
269
4
12
Order By: Relevance
“…In a 3-Tesla CMR study by Dass et al native T1 values in DCM were elevated compared to healthy volunteers and the authors concluded that native T1 mapping detects underlying disease processes beyond those assessed by LGE imaging in relatively low-risk individuals [4]. A study by Puntman et al showed similar results [53]. Also abnormally elevated ECV values were shown in patients with presence of non-ischemic DCM [54].…”
Section: Dilated Cardiomyopathy (Dcm)mentioning
confidence: 94%
“…In a 3-Tesla CMR study by Dass et al native T1 values in DCM were elevated compared to healthy volunteers and the authors concluded that native T1 mapping detects underlying disease processes beyond those assessed by LGE imaging in relatively low-risk individuals [4]. A study by Puntman et al showed similar results [53]. Also abnormally elevated ECV values were shown in patients with presence of non-ischemic DCM [54].…”
Section: Dilated Cardiomyopathy (Dcm)mentioning
confidence: 94%
“…Puntmann et al [30] reported higher precontrast T1 values for hypertrophic and nonischemic dilated cardiomyopathies at 3 T compared with controls (Hypertrophic 1.254 ± 43 ms, and nonischemic dilated cardiomyopathy 1.239 ± 57 ms vs. healthy 1.070 ± 55 ms). Also, the postcontrast T1 values (10 mins) at 3 T were shorter in hypertrophic and dilated cardiomyopathies compared with healthy (hypertrophic: 307 ± 47 ms, dilated cardiomyopathies: 296 ± 43 ms vs. controls: 402 ± 58 ms) [30].…”
Section: Mri Field Strengthmentioning
confidence: 99%
“…ECV provides quantitative estimates of diffuse myocardial fibrosis in patients with HCM, validated by surgical myocardial biopsy [46,50,51]. (Figure 3) Comparing HCM patients with healthy subjects, all T1-mapping parameters (native T1, post-contrast and ECV) prove highly accurate; however, the native T1 value shows the greatest discriminatory power, with a diagnostic accuracy of 98% [52].…”
Section: T1 Mapping In Hcmmentioning
confidence: 99%